The equation is #of sides x (#of sides - 3) divided by 2. Equation: N x (N-3) 2
5y + 1 = 4y - 1 Subtract 4y from both sides of the equation. y + 1 = -1. Add 1 to both sides of the equation. y + 2 = 0 Subtract 2 from both sides of the equation. y = -2
4 - x = 24 = 2 + x (add x to both sides of the first equation)2 = x (subtract 2 from both sides of the second equation)
You don't need square roots for this, and there is no use for them in this context. You simply divide both sides of the equation by 2.You don't need square roots for this, and there is no use for them in this context. You simply divide both sides of the equation by 2.You don't need square roots for this, and there is no use for them in this context. You simply divide both sides of the equation by 2.You don't need square roots for this, and there is no use for them in this context. You simply divide both sides of the equation by 2.
x+2x+14=5x+2.......... Given 3x+14=5x+2.............. Combine like terms 3x+12=5x.................. Subtract 2 from both sides of the equation 12=2x........................ Subtract 3x from both sides of the equation 6=x............................ Divide both sides of the equation by 2
The Accounting Equation is Assets=Liabilities + Owner's Equity?
The equation is #of sides x (#of sides - 3) divided by 2. Equation: N x (N-3) 2
you did the mathh wrong and must re-do it
The accounting equation is as follows: Assets = Liabilities + Stockholder's Equity
The fundamental accounting equation: Assets = Liabilities + Equity, is the basis for all financial accounting measurements.
The accounting equation displays the relationship between capital, liabilities and the assets. The accounting equation shows that the assets are a sum of the liabilities and the invested capital.
Equality on the accounting equation is that Assets equal liabilities + owner's equity
It is based on Accounting Principle of Dual Aspect of Money http://www.freembanotes.in/finance/accountancy/30-accounting-equation
5y + 1 = 4y - 1 Subtract 4y from both sides of the equation. y + 1 = -1. Add 1 to both sides of the equation. y + 2 = 0 Subtract 2 from both sides of the equation. y = -2
The debits in the accounting equation increase the amount that appears on the left side. The credits in the accounting equation do the opposite and increase any amount that appears on the right side.
4 - x = 24 = 2 + x (add x to both sides of the first equation)2 = x (subtract 2 from both sides of the second equation)
1. Assets 2. Liabilities 3. Owners or Shareholder Equity